Wastewater and drinking water treatment by membrane processes: from laboratory to pilot-scale - Lopes, Mafalda Tomé Pessoa (2019)
The concern with water quality problems worldwide has led to the improvement of water/wastewater treatment processes. In this PhD project, industrial water and drinking water treatments using membrane processes were investigated in three different case studies. The main aim of these works was the assessment, optimisation and validation of the process’s technologies for the respective case studies. These studies included in a laboratory stage followed by a pilot-scale stage. The first case study contemplates residual water from a rubber industry presenting high chemical oxygen demand (COD). The impact of retrofitting of the existent wastewater treatment process with the replacement of the previously used evaporator with an integrate system (nanofiltration+ evaporator), was evaluated. Two modes of operation were considered, batch and continuous, depending on the daily flowrate of water to be treated in this industry. The second case study addresses surface water treatment, for production of drinking water with a high chemical and microbiological quality, required by the current legislation. The research was focused on the validation of a multibarrier system incorporating nanofiltration and UV photolysis performed at three different locations of the surface drinking water production line. The third case study focuses on a novel treatment process dealing with groundwater contaminated by arsenic (in its inorganic arsenate form) with the purpose to be applied in rural areas located far from centralised drinking water supply infrastructures. It has been a challenge worldwide to treat arsenic contaminated drinking water in order to meet the current strict regulation standard for As. In this research, an ion exchange membrane process, integrating Donnan dialysis with precipitation of this target pollutant was proposed. This work explored the feasibility of arsenic removal from water streams containing sulphate, which strongly competes with arsenate and is preferentially transported through strong-base anion-exchange membranes. Subsequently, the optimisation of arsenic removal from drinking water by the process proposed was performed by using a response surface methodology (RSM). A systematic analysis of the three case studies was carried out and is presented in this thesis in order to provide a deeper insight into the treatment processes studied (theoretical and practical aspects), which makes the proposed solutions also applicable to other water/wastewater treatment cases, facing similar challenges.